Redox-active organic molecule encapsulated MWCNT catholyte for aqueous zinc flow battery - Priyanka P. Bavdane; Vidhiben Dave; Sooraj Sreenath; Pooja Madiyan; Rajaram K. Nagarale (Next Energy)
Rechargeable zinc-ion batteries show great promise for sustainable energy storage applications. Halogen cathodes are conventionally deployed for zinc-based flow batteries. However, poor solubility of polyhalide complexes during battery operation results in poor Coulombic efficiency and short cycle life. Recent research has focused on discovering new cathode materials. In this study, we explore the use of redox-active organic molecules (ROM), 7,7,8,8-tetracyanoquinodimethane (TCNQ), hydroquinone (HQ), and 2,2,6,6-tetramethylpiperidinyloxy (TEMPO) thermally encapsulated within multiwalled carbon nanotubes (MWCNT) as effective cathode materials for zinc flow battery. The encapsulation of redox-active molecules into MWCNT, that is, TCNQ@MWCNT, HQ@MWCNT, and TEMPO@MWCNT was confirmed through detailed spectroscopic and microscopic characterization. The electrochemical activity of materials was analyzed by cyclic voltammetry experiments. Three batteries were assembled; the anolyte solution contained aqueous zinc salt, while 5.0% dispersion of TCNQ@MWCNT/HQ@MWCNT/TEMPO@MWCNT in aqueous supporting electrolyte served as catholyte. Remarkably, all the assembled batteries demonstrated exceptional cycling stability and high Coulombic efficiencies at an applied current density of 1 mA cm⁻². The assembled batteries also achieved ∼90.0% capacity utilization of the theoretical capacity, which was 233.0, 225.2, and 129.4 mAh g−1 for Zn/TCNQ@MWCNT, Zn/HQ@MWCNT, and Zn/TEMPO@MWCNT batteries, respectively. The availability of the materials used, along with the absence of hazardous, flammable, or volatile organic electrolytes, positions this approach as a superior choice for catholyte applications in zinc flow batteries (ZFBs).